Design of Demodulation Circuit And Arduino Uno Microcontroller Syncronization For Capacitance Sensor - Menasita, Menasita; Mirnawati, Mirnawati; Sulistijono, Sulistijono (LPPM ITK, 2019)
An AC signal is produced by oscillator or a similar circuit that includes demodulation. In addition to thedemodulation circuit, there is also need interface circuit which include signal conditioning, signal processing anddata acquisition. So that, the frequency can be read digitally. The purpose of this research was to createdemodulation circuit in form of colpitts-crystal oscillator and microcontroller. This research carried out severalstage. There are making colpitts-crystal oscillator, microcontroller synchronization, data retrieval and processingoutput. The DC voltage variations are 3.2 V, 9 V and 15.9 V and capacitor variations are 470 pF, 4.7 nF and 33nF. Output data in form of frequencies measured by using oscilloscope. Futhermore, the data is tested for accuracyand precision. From the test result using 470 pF, 4.7 nF and 33 nF capacitors when given 3.2 V input voltage, theprecision values were 91.35%, 93.06% and 96.17% and the accuracy value were 97.72%, 97.96%, and 98.17%.For 9 V input voltage, the precision values were 99.82%, 97.67% and 97.52% and the accuracy value were 99%,98.90%, and 98.92%. Whereas 15.9 V input voltage, the precision values were 93.43%, 96.92% and 93.66% andthe accuracy value were 98.08%, 98.75%, and 97.60%. From these data, it can be concluded that a good voltagevalue used in this ciecuit is 9 V with 470 pF capacitor where the precision value was 99.82% and the accuracyvalue was 99%.